Dampak Revitalisasi Dalam Meningkatkan Daya Tarik dan Penjualan Produk Lokal pada Pedagang Muslim Di Pasar Citra Niaga Samarinda - Muhammad Hasbi; Diah Paramita Kusuma Wardani; Norvadewi Norvadewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
Revitalization is a major effort expected to revitalize an area, particularly Citra Niaga Market, by modernizing the infrastructure and facilities within the traditional market without losing its traditional character and appeal. The primary goal of market revitalization is to improve the welfare of vendors, revitalize its economic appeal, and modernize the existing infrastructure. This study aims to analyze the impact of revitalization on increasing the appeal and sales of local products. This research focuses on the post-revitalization impacts. The method used is descriptive qualitative with a case study approach. Data were collected through observations at Citra Niaga Market in Samarinda, interviews with market managers, Muslim vendors, and visitors, as well as documentation from sources such as news reports and previous research to support the research findings. The data analysis technique used was data triangulation, which involved data reduction, data presentation, and drawing conclusions. The results indicate that Citra Niaga Market in Samarinda is a shopping destination for local products with significant potential as a highly attractive tourist destination. The increase in sales of local products from Muslim vendors at Citra Niaga Market in Samarinda has not been evenly distributed across the market. The impact of the revitalization is felt in the accessibility and adequate facilities, cleanliness and comfort, and more organized kiosk layout. Overall, the revitalization of Citra Niaga Market has increased its appeal and provided a positive economic impact for Muslim traders, although optimization in terms of equity and sustainable management is still needed. Keywords: Revitalization1, Attractiveness2, Sales3.